Relationship between dietary thiamine, riboflavin, and niacin intake and hypertension subtypes: A cross-sectional study from the 1999–2023 - Siqi Ma; Qu Jin; Keying Yu; Hezeng Dong; Yanmei Lu; Liping Chang (PLoS ONE, 2026)
Background This cross-sectional study aimed to investigate whether vitamin B intake (thiamine, riboflavin, niacin) influences different hypertension subtypes and which subtype exhibits a more profound effect. The objective was to determine whether different vitamins should be supplemented according to specific hypertension subtypes. Methods This cross-sectional study encompassed data from twenty-five years spanning 1999–2023, focusing on individuals with hypertension who possessed complete 24-hour dietary intake records and clinical assessments. Their total intake was disaggregated into two dimensions—‘food sources’ and ‘supplement sources’—for separate estimation. Multivariable logistic regression models were employed to determine the odds ratios (OR) and 95% confidence intervals (95% CI) for associations between thiamine (vitamin B1), riboflavin (vitamin B2), and niacin (vitamin B3) intake and hypertension subtypes in subjects with hypertension versus those without. The relationship between nutrient intake and hypertension subtype risk was assessed using multivariable logistic regression models. To balance baseline characteristics, propensity score weighting was applied, followed by logistic regression. Logistic regression identified inflection points, with threshold effects assessed through piecewise logistic analysis. Inflection points were verified using likelihood ratio tests and bootstrap resampling. Heterogeneity and interactions between subgroups were evaluated via logistic regression models and likelihood ratio tests, respectively. Results Analysis of NHANES data revealed significant demographic and dietary pattern differences between distinct hypertension subtypes. Multivariate regression analysis indicated that the initial positive association between dietary B vitamins and isolated systolic hypertension (ISH) largely disappeared upon adjustment, suggesting confounding effects from covariates such as age and comorbidities. Conversely, a strong independent positive association was observed between high riboflavin intake and systolic-diastolic hypertension (SDH). In the fully adjusted model, each unit increase in riboflavin was associated with a 25% increase in SDH risk (OR=1.25, 95% CI 1.05–1.49), exhibiting a significant dose-response trend. A potential threshold effect was observed near a 6 mg/day dose, beyond which the risk increment levelled off. Thiamine exhibited a potential non-linear association with SDH risk across quartiles, whereas no significant association was observed for niacin. Subgroup analyses indicated that the association between the three B vitamins and ISH risk was stronger among non-smokers and was influenced by gender (thiamine) and BMI (niacin). Conclusions This study reveals subtype-specific hypertension risk factors. Whilst crude analyses indicated an association between B-vitamin intake and hypertension, multivariate adjustment revealed only riboflavin exhibited a significant independent positive correlation with the SDH subtype, suggesting it may represent a unique dietary-related factor for this subtype. The initial association with the ISH subtype was primarily attributable to confounding factors. The findings underscore the necessity for comprehensive adjustment and subtype stratification in nutritional epidemiology. The identified interaction with smoking status indicates that lifestyle factors play a crucial moderating role in dietary risk associations. The plateauing of SDH risk at high riboflavin levels suggests the need to further investigate potential threshold effects. These findings deepen our understanding of the relationship between diet and hypertension, emphasising that associations are not universally applicable across all manifestations of hypertension but are context-dependent. These findings suggest a complex relationship between riboflavin intake and hypertension subtypes, underscoring the need for personalized dietary approaches rather than universal supplementation. This study highlights the importance of maintaining balanced nutrition for cardiovascular health.